An investigation of the electronic structure and optoelectronic properties of 4-((2-hydroxy-3-methoxybenzylidene)amino)-N-(thiazol- 2-yl) benzene sulfonamide - Dyari Mustafa Mamand; Dara Muhammed Aziz; Hiwa Mohammad Qadr (Конденсированные среды и межфазные границы, 2024)
Molecules of 4-((2-hydroxy-3-methoxybenzylidene)amino)-N-(thiazol-2-yl)benzene sulfonamide were investigated at varying concentrations in dimethyl sulfoxide (DMSO). Different temperatures were employed to assess bandgap energies, Tauc plots, refractive indices, optical and electrical properties, and dielectric constants. The refractive index was determined through a straightforward model based on energy gap data and subsequently compared to experimental values. For the examination of the materials’ optical properties, reflection and reflection loss at plasma frequencies were considered as they play a crucial role. Density functional theory (DFT) with a 6-311G++ (d, p) basis set and Becke’s three-parameter hybrid (B3LYP) level of theory were utilized through Gaussian software to conduct the studies. Chemical reactivity and selectivity parameters, including HOMO-LUMO, global hardness, softness, electronegativity, electrophilicity, nucleophilicity, chemical potential, bandgap energy, and electron affinity, were computed. Becke’s three-parameter hybrid exchange-correlation functional (B3LYP) level was employed for optimizing the geometry of the title molecule